Strategy for Preventing Child Marriage by Puspaga Tanjungpinang City - Febrianty, Dwi; Fitriani, Laila; Casiavera, Casiavera (Formosa Journal of Applied Sciences, 2023)
This research aims to provide assistance and education to prospective couples who want to get married when they are children in the city of Tanjungpinang. The method used in this research is a qualitative research method. In this research, to find data, interviews were conducted with PUSPAGA regarding the assistance and education provided to couples at the age of children, and it was found that the cause of marriage between couples at the age of children was pregnancy out of wedlock. So that assistance and education are provided to couples at the age of children, in order to improve parental skills and the quality of child care for couples at the age of children, as well as minimizing the occurrence of divorce and preventing the next generation from marrying at the age of children in Tanjungpinang City Regency.